2018
DOI: 10.1186/s12957-018-1418-2
|View full text |Cite
|
Sign up to set email alerts
|

Plasma levels of the proangiogenic protein CXCL16 remains elevated for 1 month after minimally invasive colorectal cancer resection

Abstract: BackgroundInflammation-induced endothelial precursor cell recruitment and angiogenesis are thought to be associated with CXCL16-CXCR6 pair activity. This study’s main purpose was to determine plasma CXCL16 levels after minimally invasive colorectal resection (MICR) for colorectal cancer (CRC); an adjunct study assessed wound fluid (WF) and plasma CXCL16 levels in a separate group of CRC patients.MethodsCRC patients who had MICR and for whom plasma was available in a tissue bank were eligible. Plasma samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…KGF may follow the concentration gradient from the wound (high KGF levels) to the circulation (low KGF levels). This is in keeping with many of the other proteins, mentioned above, whose plasma levels have been shown to be persistently increased after colorectal resection (11,15,16,18,19,(21)(22)(23)(24)(25)(26). In a study that simultaneously assessed plasma and wound fluid levels of 8 of these "long duration" proteins after colorectal resection, it was demonstrated that the mean wound levels of the proteins were 3 to 40 times higher than their corresponding plasma concentrations which, in turn, were significantly elevated from their pre-operative baseline blood levels (27).…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…KGF may follow the concentration gradient from the wound (high KGF levels) to the circulation (low KGF levels). This is in keeping with many of the other proteins, mentioned above, whose plasma levels have been shown to be persistently increased after colorectal resection (11,15,16,18,19,(21)(22)(23)(24)(25)(26). In a study that simultaneously assessed plasma and wound fluid levels of 8 of these "long duration" proteins after colorectal resection, it was demonstrated that the mean wound levels of the proteins were 3 to 40 times higher than their corresponding plasma concentrations which, in turn, were significantly elevated from their pre-operative baseline blood levels (27).…”
Section: Discussionsupporting
confidence: 80%
“…The majority of plasma protein changes after surgery persist hours or days (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), however, in the last decade, increases in the blood levels of at least 12 proangiogenic proteins have been noted to persist for 3-5 weeks after resection of colorectal cancer (CRC). Included on this list are vascular endothelial growth factor (VEGF), angiopoeitin-2 (Ang-2), placental growth factor (PIGF), soluble vascular adhesion molecule-1 (sVCAM-1), Angiopoietin like 4 (ANPTL4), monocyte chemotactic protein-1 (MCP-1), human chitinase 3-like 1 (Chi3L1), matrix metalloproteinase-2(MMP-2),matrix metalloproteinase-3 (MMP-3), matrix metalloproteinase-3 (MMP-7), Chemokine (C-X-C motif) ligand 16 (CXCL 16), and Interleukin 8 (IL-8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, elevated plasma levels of CXCL16 may encourage tumour angiogenesis in the first month after MICR and could be a useful marker for screening tumour recurrence after resection (Ref. 65). Also, Shibata et al .…”
Section: Cxcl16/cxcr6 Expression As Diagnostic and Prognostic Markers In Cancersmentioning
confidence: 99%